SIKAP TERHADAP MARKETING MIX DAN PROSES PENGAMBILAN KEPUTUSAN PEMBELIAN KONSUMEN PADA DAEBAK FAN CAFE, DEPOK - Winda Rahmalia; Dedi Budiman Hakim; Rico Rizal Budidarmo (School of Business, Bogor Agricultural University (SB-IPB), 2016)
Nowadays, Korean culture is dominating the global lifestyle including that of Indonesia. There are a variety of Korean restaurants, one of which adopts the concept of Korean Fan Café which is used as a gathering forum for the Korean popular culture fans. The aims of this study are to obtain information related to consumer demographics and analyze attitudes toward marketing mix in the consumer decision making in Daebak Fan Café. Thus, descriptive and chi-square analyses were utilized as the methods of data analysis. The results showed that the majority of consumers of Daebak Fan Cafe are women aged 21-30 years, with single status. Most of the consumers are students with pocket money ranging from ≤ Rp 1,000,000 per month and reside in Depok. There are two demographic variables noted in the study i.e. the consumers’ ages and incomes which are related to the marketing mix variables; covering social groups, products, and promotions, while the employment status variable only relates to the promotions.Keywords: demography, fan cafe, decision making, marketing mix, chi-squareABSTRAKAkhir-akhir ini, budaya Korea sangat mendominasi gaya hidup masyarakat dunia, termasuk di Indonesia. Berbagai restoran Korea dibangun, alah satunya dengan konsep Korean Fan Cafe yang merupakan wadah berkumpul para penggemar budaya populer Korea. Tujuan studi ini adalah memperoleh informasi yang berkaitan dengan demografi konsumen, dan menganalisis sikap terhadap marketing mix pada pengambilan keputusan konsumen di Daebak Fan Cafe. Metode analisis data dilakukan menggunakan analisis deskriptif dan analisis chi-square. Hasil penelitian menunjukkan sebagian besar konsumen yang datang ke Daebak Fan Cafe mayoritas adalah wanita dengan usia 21–30 tahun dengan status belum menikah. Mayoritas konsumen adalah pelajar dengan uang saku ≤ Rp1.000.000 per bulan dan berdomisili di Depok. Studi ini mencatat bahwa terdapat dua variabel demografi yaitu usia dan pendapatan yang berhubungan dengan variabel marketing mix yaitu sosial-grup, produk, dan promosi, sedangkan untuk variabel status pekerjaan hanya berhubungan dengan promosi.Kata kunci: demografi, fan cafe, pengambilan keputusan, marketing mix, chi-square